2004
DOI: 10.1002/jat.945
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of caffeic acid phenethyl ester on doxorubicin‐induced cardiotoxicity in rats

Abstract: The prevention of doxorubicin (DXR)-induced cardiotoxicity may be helpful to improve future DXR therapy. The aim of this study was to investigate the cardio-protective effects of caffeic acid phenethyl ester (CAPE), an antioxidant agent, on DXR-induced cardiotoxicity. Rats were divided into three groups and treated with saline, DXR and DXR + CAPE. Rats were treated with CAPE (10 micromol x kg(-1) day(-1) i.p.) or saline starting 2 days before a single dose of DXR (20 mg x kg(-1) i.p.). Ten days later, haemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 30 publications
6
78
1
Order By: Relevance
“…Parlakpınar et al (10) reported that CAPE acts in the heart as a potent scavenger of free radicals to prevent the apoptotic effect of myocardial ischemia/reperfusion injury. The authors showed that CAPE inhibits lipid peroxidation and suppresses oxidative stress (9,11). It was shown in the previous studies that CAPE preserved heart tissue from doxorubicin-induced cardiac damage (11).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Parlakpınar et al (10) reported that CAPE acts in the heart as a potent scavenger of free radicals to prevent the apoptotic effect of myocardial ischemia/reperfusion injury. The authors showed that CAPE inhibits lipid peroxidation and suppresses oxidative stress (9,11). It was shown in the previous studies that CAPE preserved heart tissue from doxorubicin-induced cardiac damage (11).…”
Section: Introductionmentioning
confidence: 95%
“…The authors showed that CAPE inhibits lipid peroxidation and suppresses oxidative stress (9,11). It was shown in the previous studies that CAPE preserved heart tissue from doxorubicin-induced cardiac damage (11).…”
Section: Introductionmentioning
confidence: 95%
“…A single dose administration of Dox (10 mg kg −1 ) caused a significant increase in MDA content (an index of lipid peroxidation) in cardiac tissues and decrease in myocardial GSH compared to control group indicating an increase in oxidative stress. (Fadillioglu et al, 2004;Patil and Balaraman, 2005). Administration of LSFJ improved the biochemical marker levels indicating decrease in oxidative stress as evident by increased level of GSH and SOD with decreased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Results of our study confirm the contribution of inflammation in DOX-induced cardiotoxicity, because anti-inflammatory agents can at least, in part, reduce DOX-induced cardiotoxicity. It has been suggested that DOX also induces endothelial dysfunctions (Kotamraju et al, 2002;Wolf and Baynes, 2006), because it has been demonstrated in vivo that treatment with DOX caused oxidative stress and myeloperoxidase (MPO) activity (Fadillioglu et al, 2004). N e -(carboxymethyl)lysine can be formed by oxidative stress (Baynes, 1991;Nerlich and Schleicher, 1999), and also by the enzyme MPO (Anderson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%